Evaluation of IT Governance at ICT UNISM Using COBIT 5: EDM01, APO01 - Hapsari, Erwenda Tri; Delakamin, Putri Ika; Ramdhani, Amanda Putri; Sabrila, Trifebi Shina; Latif, Abdul; Lindawati, Ratna (INSTALL: Information System and Technology Journal, 2024)
Framework with its flexible, holistic, and principle-based nature, COBIT 5 can be implemented according to the specific needs of various types of organization and companies. The objective of this study is to analyze and determine the maturity level of IT governance at ICT UNISM. ICT plays a crucial role as a key driver of digital transformation and economic development, particularly in enhancing efficiency and effectiveness in learning processes. The IT governance elements in COBIT 5 are designed to evaluate stakeholder needs, conditions, and options. The method used to obtain data and information on the IT governance processes at ICT UNISM involves surveys and direct interviews. The COBIT 5 domains used in this study are Evaluate, Direct, and Monitor (EDM) and Align, Plan, and Organize (APO). The evaluation results identified a gap in the EDM01 process domain with a gap of 2, while the APO01 process domain had a gap value of 1.37. The overall average gap value was at level 3, indicating that at ICT UNISM, the processes in the EDM01 and APO01 domains are managed, meaning that the processes are executed in a controlled manner, with defined and maintained outcomes. For future research, more process domains can be included, covering both Governance and Management areas, allowing for a more comprehensive audit process using the COBIT 5 framework.